Survey of Lesser Black-backed Gull (Larus fuscus Linnaeus, 1758) migration and wintering in the Azov-Black Sea region - Руденко, А. Г. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
This article is completed on the analysis of the published and original materials about migrations and wintering of Lesser Black-backed Gull (Larus fuscus L.) in the Аzov-Black Sea coasts region from the end ХІХ century to present days. The change of numbers, spatial distribution and phenological features during migration and wintering are analyzed. The special attention is spared to the analysis of the data, got by the author as a result of count works in the district of Теndra, Yagorlitsky and Dzharilgatchsky bays of the Black sea in 1984–2014 years. At the Azov-Black Sea region in the late nineteenth and the first half of the twentieth century, the number of Lesser Black-backed Gull was relatively low. Gradually, it grew up and in 1950–1970-ies was obviously maximal, and then a gradual decline began. This is consistent with trends in the total number of subspecies in Europe.